Art and Science: Encounters and Learning Between University Students and Primary School Students - Curvelo, Eliana (2024)
The Academic Integration Week (SINTA) is a component of the curriculum called Curricularization of Extension in the Veterinary Medicine Course, in which teachers, students and postgraduates committed to society develop integration projects with the local community. The Project-Based Learning (PBL) methodology is used, with a view to apply theoretical concepts in such a way that the information translates into knowledge for both the university and society, as well as action-research with the aim of teaching the student to be a researcher in a reflective process. Specifically, the aim of this project was to present science in a playful way to approximately ninety elementary school students - final years (7th and 8th grades), whose percentage of adequate learning has been inadequate. Postgraduate and undergraduate students were involved in the activity by demonstrating microorganisms using electron microscopes so that primary school students could learn the basic concepts of science. The knowledge of science was learned in a practical way and the perceptions of the images were recorded with illustrations, integrating the knowledge of science with that of art, resulting in the apprehension of the information taught and transformed into knowledge to be applied in everyday life.